Institutions Are Not Rules: Realigning the Ontology Behind Theories of Change. - Castro, Henrique A (Political Studies, 2024)
Historical institutionalism has fruitfully moved beyond its initial focus on institutional effects to incorporate change. I argue, however, that the resulting advances have become misaligned with their conceptual bases. "Institutions as rules" was a useful first approximation, but it cannot accommodate changes in institutionalized practices occurring while sources of law remain the same. I propose reconceiving legal rules (material objects) and institutions (behavioral dispositions) as distinct elements that nonetheless remain fundamentally associated through the belief-shaping actions of specific groups. While rules change with the introduction of officially recognized materials, legal institutions change in response to new beliefs regarding what could pass as officially permissible. Far from a mere exercise in conceptual precision, the proposals draw distinctions that matter for description and explanation. In that regard, I show how the current literature mischaracterizes court-led change and how we might advance on the underexplored issue of collective meaning-making amidst unequal legal expertise.